(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2021)
Village Owned Enterprises (BUM Desa) are economic institutions in rural areas that are fully managed by village communities aiming at the welfare of the village community. This study aims to find out the performance, performance inhibiting factors, and conceivable efforts to improve the performance of BUM Desa Catur Mandiri managers. The study design used descriptive qualitative. To find out the performance of the managers BUM Desa using performance indicators of productivity, service quality, responsiveness, responsibility, and accountability. The results of the study show that the performance of the managers of BUM Desa is still low because three of the five indicators have not been met (productivity, service quality, and responsiveness). The factors hampering the performance of the managers of BUM Desa Catur Mandiri are human resources, internal coordination, lack of initiative to innovate products and marketing, mastery of technology, services that are not yet customer-oriented, lack of ability to explore community aspirations in doing business, lack of government support, and low village community participation. Efforts that must be made by the managers of BUM Catur Mandiri Village to improve their performance include increasing the quality of human resources, affirming the Standard Operating Procedure, developing the concept of social entrepreneurship and empowering community-based participation in running their business activities.